PENGEMBANGAN E-BOOKLET TEMA JAJANAN JUMBREK BERBASIS ETNOSAINS UNTUK MENINGKATKAN LITERASI SAINS - Stabita, Sabrina Jihan; Rakhmawan, Aditya; Wahyuni, Eva Ari; Putra, Dwi Bagus Rendy Astid; Mu'aziyah, Siti Eneng Sururiyatul (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2025)
This study aims to determine the validity of the e-booklet jumbrek snacks ethnoscience-based, readability, response, and improvement of students' scientific literacy. This type of research is Research n Development (RnD) using the ADDIE model. Sampling using purposive sampling technique. The subjects of the study were 36 students of class VIII A of SMPN 1 Kalitengah, Lamongan Regency at the implementation stage. The results show that: (1) the e-booklet has a very high validity, with media validity of 93.75% and material validity of 86.81%; (2) the readability score is 89.51%, categorized as very good; (3) students’ responses reach 89.61%, also categorized as very good; and (4) the e-booklet improves science literacy, with an average N-Gain of 0.66, categorized as moderate. It can be concluded that the ethnoscience-based e-booklet on jumbrek snacks is very valid, easy to understand, well-received by students, and effective in improving science literacy.